Review of Teacher Educators as Critical Storytellers: Effective Teachers and Windows and Mirrors - Miller, Libbi (Educational (Re)naissance, 2022)
Teacher Educators as Critical Storytellers: Effective Teachers and Windows and Mirrors is a collection of curated of stories that pushback against the narratives that define a “good” teacher. Told through through critical storytelling methodology, the book draws on the “windows” and “mirrors” framework to invite multiplicies into the understanding of teachers. The book successfully contributes to a broader, inclusive and culturally sustaining narrative of teaching and education related professions and can be implemented as a text for learning with both preservice and inservice teachers.